أساليب الخطاب القرآني في تحقيق مقصد حفظ المال : Methods of Quranic discourse in achieving the purpose of saving money - Elatrash, Radwan Jamal Yousef (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
المدقق الخبير يجد نقصاً في الدراسات العلمية حول أساليب الخطاب القرآني في تحقيق مقصد حفظ المال. لهذا فإن هذه الورقة تتناول مقصداً واحداً هو مقصد حفظ المال من خلال الأساليب المتنوعة لتحقيقه وما يميزه عن غيره. ومن المعلوم أن مقاصد الشريعة الخمسة وكلها تسعى لتحقيق غرض واحد هو: درء المفاسد وجلب المصالح، ومن أهم المقاصد الشرعية التي يجلب بها المصالح ويدرأ بها المفاسد لكل الخلائق على السواء هو مقصد حفظ المال. لذا فإن هذه الورقة تهدف إلى إثارة أساليب الخطاب القرآني من خلال الاستقصاء والتركيز على كيفية عرض هذه الأساليب الدالة على حفظ المال وتنميته. وسيراً مع طبيعة الموضوع فإن البحث يقتضي أن يعتمد على المنهج الاستقرائي ثم المنهج التحليلي. وقد خلص البحث إلى أن القرآن الكريم في تنوع أساليبه أكد على حفظ المال، ورغب بكتابة الدين والإشهاد وقبول شهادة النساء صيانة لحقوق الناس من الأموال والأعراض. كما أثبت البحث أن هناك أساليب أكدت أن إتلاف المال بدون غاية نبيلة ومقاصد سامية تجلب المصالح وتدرأ المفاسد فإن ذلك يعد من المحرمات التي نهى عنها الخطاب القرآني. The expert examiner learns need of scientific studies on the methods of Quranic discourse in accomplishing the purpose of saving money. Therefore, this paper deals with one objective, which is the objective of saving money through various methods of achieving it, and what distinguishes it from others. It is well known that the five objectives of Sharia, all of which seek to achieve one goal, are warding off corruption and bringing about benefits. Therefore, this paper aims to raise the methods of Quranic discourse through investigation and focus on how to present these methods that indicate the preservation and development of money. In line with the nature of the research, it requires to depend on the inductive method and then the analytical method. The research concluded that the Holy Qur’an, in its diversity of methods, emphasized the preservation of money, and desired to write down the debt, to testify, and to accept the testimony of women, in order to preserve the rights of people in terms of money and honor. The research also proved that there are methods that confirmed that wasting money without a noble purpose and lofty purposes brings interests and ward off evils, as this is one of the things forbidden by the Qur’anic discourse.